A Review on Preferential Oxidation of Carbon Monoxide in Hydrogen Rich Gases - A. Mishra; Ram Prasad (Bulletin of Chemical Reaction Engineering & Catalysis, 2011)
In this review, recent works on the preferential oxidation of carbon monoxide in hydrogen rich gases for fuel cell applications are summarized. H2 is used as a fuel for polymer-electrolyte membrane fuel cell (PEMFC). It is produced by reforming of natural gas or liquid fuels followed by water gas shift reaction. The produced gas consists of H2, CO, and CO2. In which CO content is around 1%, which is highly poisonous for the Pt anode of the PEMFC so that further removal of CO is needed. Catalytic preferential oxidation of CO (CO-PROX) is one of the most suitable methods of purification of H2 because of high CO conversion rate at low temperature range, which is preferable for PEMFC operating conditions. Catalysts used for COPROX are mainly noble metal based; gold based and base metal oxide catalysts among them Copper-Ceria based catalysts are the most appropriate due to its low cost, easy availability and result obtained by these catalysts are comparable with the conventional noble metal catalysts. © 2011 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)